The Effect of Early-Life Environmental Exposures on Disease Phenotype and Clinical Course of Crohn's Disease in Children. (October 2018) - Lindoso, Livia; Mondal, Kajari; Venkateswaran, Suresh; Somineni, Hari; Ballengee, Cortney; Walters, Thomas; Griffiths, Anne; Noe, Joshua; Crandall, Wallace; Snapper, Scott; Rabizadeh, Shervin; Rosh, Joel; et al.
Abstract Objectives Environmental factors play an important role in the pathogenesis of Crohn's Disease (CD). In particular, by virtue of the instability of the microbiome and development of immunologic tolerance, early life factors may exert the strongest influence on disease risk and phenotype. Methods We used data from 1119 CD subjects recruited from RISK inception cohort to examine the impact of early life environment on disease progression. Our primary exposures of interest were breastfeeding in infancy and exposure to maternal, active, or passive smoke. Our primary outcomes were development of complicated (stricturing or penetrating) disease, and need for CD-related hospitalization, and surgery. Multivariable logistic regression models were used to define independent associations, adjusting for relevant covariates. Results Our study cohort included 1119 patients with CD among whom 15% had stricturing (B2) or penetrating disease (B3) by 3 years. 331 patients (35%) and 95 patients (10.6%) required CD-related hospitalizations and surgery respectively. 74.5% were breastfed in infancy and 31% were exposed to smoking among whom 7% were exposed to maternal smoke. On multivariable analysis, a history of breastfeeding was inversely associated with complicated (B2/B3 disease) 0.65, CI 95% 0.44–96;P  =  0.03) in pediatric CD. Maternal smoking during pregnancy was associated with increased risk of hospitalization during the 3-year follow-up period (OR 1.75, CI 95% 1.05–2.89;P  = 0.03). Conclusions Early life environmental factors influence the eventual phenotypes and disease course in CD.